First report of Bartonella henselae infection in a cat in North Macedonia - Shikoska, Ivana; Dјadјovski, Igor; Krstevski, Kiril; Hristovska, Zagorka Popova; Janevski, Aleksandar; Rashikj, LJubica; Cvetkovikj, Aleksandar; Cvetkovikj, Iskra (Walter de Gruyter GmbH, 2023)
The genus Bartonella are fastidious, Gram-negative intracellular vector-borne bacteria with zoonotic potential. Cats have a crucial epidemiological role in the transmission of Bartonella henselae, the primary causal agent of cat-scratch disease in humans. Here we describe the first report of B. henselae infection in a cat in North Macedonia after a suspected Bartonella infection in a 7-year-old boy. A combination of cultural and molecular methods for detecting B. henselae in the asymptomatic cat was used. A blood sample was cultured on a blood agar plate, where colonies became visible after nine days of incubation. The DNA of a single colony was extracted, and the isolate was confirmed as B. henselae by sequencing the bacterial 16S ribosomal RNA gene and performing a Bartonella - specific PCR. The phylogenetic analysis demonstrated 100% similarity with B. henselae sequences, clustering on a single branch and establishing a distinct group. This finding indicates that B. henselae infection in cats circulates in North Macedonia and may affect feline and human health.
Keywords: Bartonella henselae, zoonosis, public health, detection